Paradise Postponed: A Re-examination of the Green Book Proposals of 1945 - Finkel, Alvin (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1993)
AbstractDuring World War Two, all federal political parties sought to accommodate the growing demand for "welfare state" programs. Mackenzie King's Liberals successfully checked the growth of the CCF by promising a comprehensive program of cradle-to-grave security. After the 1945 election the Liberal government prepared such a program and brought it to a dominion-provincial conference whose purpose was to determine the taxation and administrative arrangements necessary for its implementation. The "conference", which became a series of mini-conferences stretched over nine months, ended without agreement. The federal government blamed recalcitrant premiers in Ontario and Quebec for the conference's failure and abandoned much of the reform program. This article argues that the federal government, in fact, wanted the conference to fail because it did not want to undertake the expenses implied in the reform proposals. After proving inflexible in dealing with provincial criticisms, it cynically and successfully manipulated events to make it appear that the provinces had killed hopes for reform. Post-war prosperity and a declining interest in reform, particularly on the part of the corporate and medical elites, contributed to the federal government's unwillingness to pursue reform vigorously.